Shotgun proteomic analysis of Yersinia ruckeri strains under normal and iron-limited conditions. (December 2016) - Kumar, Gokhlesh; Hummel, Karin; Ahrens, Maike; Menanteau-Ledouble, Simon; Welch, Timothy; Eisenacher, Martin; Razzazi-Fazeli, Ebrahim; El-Matbouli, Mansour
Abstract Yersinia ruckeri is the causative agent of enteric redmouth disease of fish that causes significant economic losses, particularly in salmonids. Bacterial pathogens differentially express proteins in the host during the infection process, and under certain environmental conditions. Iron is an essential nutrient for many cellular processes and is involved in host sensing and virulence regulation in many bacteria. Little is known about proteomics expression ofY. ruckeri in response to iron-limited conditions. Here, we present whole cell protein identification and quantification for two motile and two non-motile strains ofY. ruckeri cultured in vitro under iron-sufficient and iron-limited conditions, using a shotgun proteomic approach. Label-free, gel-free quantification was performed using a nanoLC-ESI and high resolution mass spectrometry. SWATH technology was used to distinguish between different strains and their responses to iron limitation. Sixty-one differentially expressed proteins were identified in fourY. ruckeri strains. These proteins were involved in processes including iron ion capture and transport, and enzymatic metabolism. The proteins were confirmed to be differentially expressed at the transcriptional level using quantitative real time PCR. Our study provides the first detailed proteome analysis ofY. ruckeri strains, which contributes to our understanding of virulence mechanisms ofY. ruckeri, and informs development of novel control methods for enteric redmouth disease.